The interactive effect of pro-environmental disciplinary concentration under cooperation versus competition contexts. Issue 6 (3rd July 2017) - Cuadrado, Esther; Tabernero, Carmen; García, Rocío; Luque, Bárbara
Abstract : This research explores the relevance of cooperation and students' environmental disciplinary concentration on decision-making with respect to environmental issues – specifically the use of water, a limited common-pool resource. For this purpose, 61 environmental sciences students and 46 educational sciences students played the role of farmers and made decisions about irrigating their fields in the simulation 'Irrigania.' Prior to the simulation exercise, participants were randomly assigned to an experimental condition (competition or cooperation). Results demonstrated that both a cooperation situation and students' environmental disciplinary concentration are related to the use of more pro-environmental and less selfish irrigation strategies in the simulation. Moreover, high levels of cooperation were able to counteract the lack of students' disciplinary concentration on environmental problems; inversely, high levels of disciplinary concentration on environmental problems were able to counteract the competitive situations. This study highlights the relevance of programs that provide learning of (1) cooperative contexts that may reinforce cooperative frameworks on which students could base their behaviors, and (2) broader disciplinary concentration related to environmental problems that could lead to students feeling powerful in respect of knowing how to act against those problems and, thus, behaving in less selfish ways, with positive implications for the planet.